2016
DOI: 10.1002/hed.24681
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pretreatment peripheral blood markers in paranasal sinus cancer: Neutrophil-to-lymphocyte and platelet-to-lymphocyte ratio

Abstract: High pretreatment NLR and PLR are associated with poor prognosis in patients affected by epithelial advanced-stage SNC. © 2016 Wiley Periodicals, Inc. Head Neck 39: 730-736, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 42 publications
(80 reference statements)
0
37
0
Order By: Relevance
“…Data from 11 studies were synthesized in the meta‐analysis for NLR and OS in patients with head and neck cancer (Table ) . An elevated NLR value was found to be significantly associated with poorer OS with HR of 1.51 (95% CI 1.32‐1.73; P < .001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from 11 studies were synthesized in the meta‐analysis for NLR and OS in patients with head and neck cancer (Table ) . An elevated NLR value was found to be significantly associated with poorer OS with HR of 1.51 (95% CI 1.32‐1.73; P < .001).…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow chart of the systematic review can be found in Figure . An initial search done using the search strategy (Supporting Materials) obtained an initial 900 results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of the association between platelet count and prognosis of patients with HCC showed that thrombocytopenia is associated with poor survival. Turri-Zanoni et al 66 reported that higher PLR and NLR were associated with poor prognoses of paranasal sinus cancers, including adenocarcinoma, other carcinomas, olfactory neuroblastoma, and melanoma. However, HCC is generally accompanied by liver cirrhosis, which eventually causes thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria regarding tumor site, treatment modalities, and clinical stage were different. 66,68 Sixth, the cutoff values for platelet count or PLR were inconsistent among individual studies, which could have resulted in heterogeneity. Some studies excluded patients with conditions that could affect hematologic markers (eg, acute inflammation and autoimmune disease), 34,35,[43][44][45]51 although other studies did not use such criteria.…”
Section: Discussionmentioning
confidence: 99%